2020
DOI: 10.1128/jcm.01443-19
|View full text |Cite
|
Sign up to set email alerts
|

Test Accuracy of Human Papillomavirus in Urine for Detection of Cervical Intraepithelial Neoplasia

Abstract: The objective was to assess the diagnostic test accuracy of high-risk human papillomavirus (hrHPV) testing of self-collected urine and cervicovaginal samples for the detection of cervical intraepithelial neoplasia grade 2 or higher (CIN2+). We recruited a convenience sample of women 25 to 65 years of age who were undergoing clinically indicated colposcopy at two medical centers in North Carolina between November 2016 and January 2019. Women with normal cytology results and positive hrHPV results were also recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…A recent investigation ( 26 ) comparing histologic findings and triple HPV results in women undergoing colposcopy revealed that urine-based HPV testing was somewhat less sensitive in identifying women with high-grade CIN, compared to VSS and provider-sampled HPV results, similarly to our study. Our samples were from the initial urine stream, thought to contain highest concentrations of diagnostically relevant components ( 27 ) and to be more accurate for detecting cervical HPV than mid-stream or end-stream samples ( 28 ).…”
Section: Discussionsupporting
confidence: 80%
“…A recent investigation ( 26 ) comparing histologic findings and triple HPV results in women undergoing colposcopy revealed that urine-based HPV testing was somewhat less sensitive in identifying women with high-grade CIN, compared to VSS and provider-sampled HPV results, similarly to our study. Our samples were from the initial urine stream, thought to contain highest concentrations of diagnostically relevant components ( 27 ) and to be more accurate for detecting cervical HPV than mid-stream or end-stream samples ( 28 ).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, data from 30 combinations for urine and 25 combinations for clinician-collected samples were included in the meta-analysis, totaling to 11,159 and 10,774 women for each collection method, respectively. For the urinary HPV test studies, generally healthy women were enrolled in 4 combinations from 3 studies [ 15 29 31 ], whilst women who were referred to colposcopic clinics were enrolled in 26 combinations from 17 studies [ 7 12 13 14 16 17 18 19 20 21 22 23 24 25 26 28 30 ]. Women undergoing conization for CIN were enrolled in only one study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…This initial urine stream washes away, and hence collects, HPV-containing mucus and debris from exfoliated cells from the female genital organs lining the urethra opening. Indeed, recent clinical trials 4 collecting urine using a standardized sample collection protocol which includes use of FV urine and DNA preservative demonstrate higher hrHPV test agreement [15][16][17][18][19] and clinical sensitivity [9,12,[20][21][22] in self-collected urine versus cervical samples compared to trials where random or midstream urine was collected or not immediately preserved [23][24][25]. Although there are over 250 commercial HPV tests available on the global market to date, only few tests' performance are clinically validated for screening with an HPV assay according to either the Meijer guidelines (n=13), United States Food and Drug Administration (FDA) standards (n=2), or World Health Organization (WHO) prequalifications (n=3) [3].…”
Section: Introductionmentioning
confidence: 99%